Views on unassisted childbirth among mothers at a teaching hospital in Kuala Lumpur, Malaysia - Aniza Ismail,; Nur Farahani Anas,; Neo, Shun Qin; Najwa Hayati Ab Ghani,; Muhammad Amir Ridzwan Mahadi,; Nur Izatul-Aisyah Zainal Azeman,; Leny Suzana Suddin,; Nor Afiah Mohd Zulkefli,; Anisah Baharom, (Penerbit Universiti Kebangsaan Malaysia, 2021)
A cross-sectional study was conducted among mothers visiting clinic in UKMMC from 1st to 19th August 2016 to acquire opinions on unassisted childbirth and the determinant factors among mothers at a teaching hospital. Structured questionnaires were used in assessing their opinions on unassisted childbirth. A total of 259 respondents were recruited, 229 of them who met the inclusion criteria were included for analysis. Majority (87.3%) was Malay and 98.7% of respondents were more than 25 years old. The prevalence for mothers who agreed with unassisted childbirth was 6.6%. Bivariate analysis showed Malay (p=0.013) and non-working mothers (p=0.000) are the significant factors. There was no significant association between opinions on unassisted childbirth and quality of government healthcare services. Multivariate analysis showed middle income and non-working mothers were the significant factors contributing to opinions on unassisted childbirth. The outcome showed minority of mothers agreed with unassisted childbirth, middle income group and non-working mothers agreed on unassisted childbirth. Dissatisfaction to the quality of care at government healthcare services was not found to be the reason for unassisted childbirth. However, there could be other factors contributing to opinions on unassisted childbirth delivery which were not studied. Community-based study should be conducted to determine the other factors.